Counseling to SD Al-Washliyah Berastagi Students Regarding Prevention and How to Deal with Body Shaming - Yunistita; Hanna Niken J Sihotang; Egidia P; Dinda S; Resaloista T (Indonesian Journal of Society Development, 2023)
The term body shaming is intended to ridicule those who have a physical appearance that is considered quite different from society in general. Maybe for some people the act of Body shaming is a joke, but if it is practiced regularly, it will undoubtedly have an effect on the victim's mentality due to shame. In this regard, it is necessary to have media to distribute information and invitations not to engage in body shaming. As a result of this counseling activity, Al-Washliyah Berastagi Private Elementary School pupils who are service participants receive education. it is hoped that later there will be an increase in awareness in selecting the topics of conversation with the interlocutor, also not paying too much attention to other people's personal matters